Matthew Riley (ed.), British Music and Modernism, 1895-1960 (2010) - Huss, Fabian (Journal of the Society for Musicology in Ireland, 2013)
Review of Matthew Riley (ed.), British Music and Modernism, 1895-1960 (Farnham: Ashgate Press, 2010). ISBN 978-0-7546-6585-4.